PELATIHAN PEMBUATAN IKLAN PEMASARAN PRODUK BERSERTA AUDIO DENGAN FORMAT WAV DAN APLIKASI WIDEO DI SMK BM BUDI AGUNG MEDAN - Ommi Alfina; Elida Tuti Siregar; Wisesa Panca Praja Damanik Ambarita (Jurnal Pengabdian Pada Masyarakat METHABDI, 2022)
Marketing advertisements usually introduce and promote a product publicly in the form of images and sounds to the public as a sales strategy to expand sales targets throughout the world. This advertising activity is a very important part of expanding sales reach by using social media platforms, one of which is multimedia-based advertising, which is a combination of graphics, animation, sound, and user interactivity. This training is aimed at students at SMK Budi Agung majoring in multimedia-based marketing in the form of practical knowledge using flash to display animation and sound using the Wideo application in WAV format. Implementation of this training as a community service program as tridharma higher education in the field of education as a routine every semester.